2017
DOI: 10.1590/0001-3765201720160803
|View full text |Cite
|
Sign up to set email alerts
|

Histopatology of the reproductive tract of Nellore pubertal heifers with genital ureaplasmosis

Abstract: In order to study and characterize the lesions in the reproductive tract of Nellore heifers naturally infected with Ureaplasma diversum and presenting granular vulvovaginitis syndrome (GVS), fragments of uterine tube, uterus, cervix, vagina and vulva of 20 animals were evaluated. The macroscopic lesions of the vulvovaginal mucosa were classified in scores of "1" mild, until "4", severe inflammation and pustular or necrotic lesions. The histopathological evaluation was performed using scores of "1" to "4", acco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Present results suggest that Mycoplasma bovigenitalium might be recognized by mononuclear cells as an aggressor faster than other mycoplasmas, what would explain his transitory effect. Our previously studies showed that vaginal samples positive for Mycoplasma bovigenitalium were always obtained from cows or heifers with a severe vaginal lesion score, denoting the acute form of the infection [7,6]. Mycoplasma bovigenitalium is described as a mastitis pathogen, and it has been suggested that the source for mastitis may be from infected vaginal discharge running down onto the udder and teats.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Present results suggest that Mycoplasma bovigenitalium might be recognized by mononuclear cells as an aggressor faster than other mycoplasmas, what would explain his transitory effect. Our previously studies showed that vaginal samples positive for Mycoplasma bovigenitalium were always obtained from cows or heifers with a severe vaginal lesion score, denoting the acute form of the infection [7,6]. Mycoplasma bovigenitalium is described as a mastitis pathogen, and it has been suggested that the source for mastitis may be from infected vaginal discharge running down onto the udder and teats.…”
Section: Discussionmentioning
confidence: 99%
“…Of the risk factors related to their occurrence in dairy cattle the concomitant infection (Mycolasma spp and Ureaplasma diversum) presented the highest odds ratio (OR, 5.67, P< 0.00010 [6]. Histopathological changes in the uterus and vagina of heifers during natural infections are characterized by mononuclear cell infi ltrations, suggesting cellular response and stimulation of infl ammatory mediators [7]. Due to the limited available information regarding the pathogenesis of these organisms, little is known about how the bovine immune system responds to this infection.…”
Section: Introductionmentioning
confidence: 99%
“…It primarily infects the respiratory and genital/reproductive tracts of cattle [ 11 , 16 , 17 ]. Although granular vulvitis is common in infected cows, the infections are either symptomatic or asymptomatic [ 18 , 19 , 20 , 21 ]. Chronic granular vulvovaginitis may progress to endometritis and result in miscarriage or infertility if not diagnosed and treated [ 22 , 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%